Speed and physiological reply in swimming, cycling and running - Benavent, J.; Madera, J.; Escudero, J.; Tella, V.; Colado, J. C. (Biomechanics and Medicine in Swimming X, 2006)
The triatlon is characterized for being a lest of effort of long duration of pace of aerobic and anaerobic intensity. To deter-mine the variations before maximum and submaximum intensities in relation to the speed, it has been studied the behavior of the heart rate and of the lactate accumulation as physiological variables, the effort perceived as psychological variable and the frequency of movements as cinematic variable. The results have showed that the metabolic exigency before maximum intensities of mixed character aerobic/anaerobic in swimming is less than in cycling and in running. The intensity of 90% of the maximum speed, comes closer to the values of the Anaerobic Threshold in the tests of swimming and cycling, being higher in the test of running. In conclusion, the percent-age of Speed does not seem to be an equivalent indicator for three disciplines to discriminate the intensity of the effort.